Analysis of the essential qualities and resources young adults must have for a successful english distance learning - Cruz Morán, Hilda Raquel
The most important aim of distance learning is to make education accessible to most people. In order to be able to perform the capacity of learning and build up knowledge the student must have an active and independent role, making decisions, acting over the contents that they are receiving, and generating new concepts based on them. It is known, however, that most students are not capable of performing such qualities in their learning practice, despite the learning genre. The general objective of this research is to classify the qualities that a distance learner must have in the English language acquisition process. Therefore, what exactly is distance learning? According to the Encyclopedia Britannica distance learning, which will now be referred to as DL also called e-learning or tele-learning, is a form of education, which involves a physical separation between the teacher and the student during instruction and the use of various technologies to facilitate student-teacher and student-student communication. Since the student is the center of distance learning, what does it take for a student to be successful with this modality? It is a must for any student that decides to try distance learning to possess certain abilities that are the foundation of distance education, like autonomy, self-management, self-monitoring and self-motivation which is crucial. A student that decides to take the challenge to learn in this fashion, has to really want it and has to be aware that he’s going to make more efforts than what is usually done in regular learning.